Spatial immune biomarkers in triple-negative breast cancer: emerging evidence, technology trade-offs, and barriers to clinical translation - Liuhai Zeng; Wei Lin; Shihang Xue; Minzhi Chen; Haiyan Wu (Frontiers in Immunology, 2026)
Triple-negative breast cancer (TNBC) is an immunogenic but clinically heterogeneous breast cancer subtype. Stromal tumor-infiltrating lymphocytes (TILs), PD-L1 expression, and tumor mutational burden provide useful but incomplete summaries of the tumor immune microenvironment. Spatial immune biomarkers retain tissue architecture and ask where immune cells are located, which cells they contact, and whether local neighborhoods are inflamed, excluded, suppressive, or organized into tertiary lymphoid structures (TLS). In this critical review, we examine CD8+ T-cell proximity, stromal versus intratumoral localization, suppressive myeloid and regulatory T-cell (Treg)-rich niches, TLS maturity, and spatial checkpoint co-expression in TNBC. We also compare multiplex immunofluorescence, multiplexed ion beam imaging by time-of-flight (MIBI-TOF), imaging mass cytometry, spatial transcriptomics, and hematoxylin-and-eosin (H&E)-based artificial intelligence in terms of spatial resolution, molecular depth, formalin-fixed, paraffin-embedded (FFPE) compatibility, scalability, reproducibility, and clinical feasibility. Most reported associations with prognosis or treatment response remain retrospective or exploratory, and their definitions are sensitive to sampling, segmentation, and threshold selection. The most clinically interpretable candidates are compartment-aware TIL measures, CD8+ T-cell-tumor proximity, and TLS-related features, but none is ready to guide treatment independently. Progress will require locked biomarker definitions, multisite analytical validation, external cohorts, and prospective trials with pre-specified spatial endpoints.